Three Visions of Humanity in Extraterrestrial Ecosystems: Klein, Kosik, Skåden - Pokrywka, Rafał (Porównania, 2022)
In the paper, three contemporary science fiction novels are compared: Die Zukunft des Mars (2013) by Georg Klein, Kameleon (2008) by Rafał Kosik, and Fugl (2019) by Sigbjørn Skåden. As possible scenarios of a future colonisation of other planets, the novels represent three different patterns of human existence in extraterrestrial ecosystems: adaptation, imitation, and indifference. They are discussed in the context of contemporary speculative narrations on human life outside of Earth.